Optimalisasi Buffer Stock Pada Inventori PT DJ Menggunakan Economic Order Quantity (EOQ) - Afra, Syeda Maria Ahmad; Firmansyah, Iqbal; Islam, Sifa Nurul (Institut Transportasi dan Logistik Trisakti, 2023)
PT. DJ is an abattoir located in DKI Jakarta. PT DJ the supplies beef needs in DKI Jakarta. In this study, researchers used two types of beef, namely neck bone and knuckle. The problem that occurs at this time is that PT. DJ does not yet have good inventory management so that the cost of procurement and supply of imported beef is high and there is often uncertainty about the supply of beef from suppliers. The existence of planning for procurement and supply of imported beef at PT. DJ to reduce procurement and inventory costs and ensure that the stock of imported beef needs in DKI Jakarta is met. This study uses the method of Economic Order Quantity (EOQ), Re Order Point (ROP), and Buffer Stock. The results of this study based on calculations using the EOQ method produce a more optimal total cost compared to the current conditions at PT. DJ